MULTICULTURAL APPROACH IN ISLAMIC EDUCATION ON STUDENTS’ LEARNING OUTCOMES AND UNDERSTANDING OF PLURALISM IN INDONESIAN SCHOOLS - Muhammad, Fikri Rizkia; Al Ayyubi, Ibnu Imam; Indrawan, Deni; Nurhikmah, Nurhikmah; Rahmawati, Siti (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Multicultural education serves as a reflective critique and exploration of these issues to pave the way for cross-cultural communication and promote fair and constructive engagement with cultural diversity; (2) Purpose of the Study: This study aims to analyze the effectiveness of the multicultural approach in Islamic religious education on students' learning outcomes and understanding of pluralistic values; (3) Methods: The research employs a mixed-methods approach with an explanatory sequential design, integrating both quantitative and qualitative analyses. The study was conducted at MI Muhammadiyah Bontobodda, SDN 23 Centre Takalar, and SD Inpres Bone, involving a sample of 30 third-grade students from each school, selected through purposive sampling. The learning approaches examined in this study include multicultural, humanistic, and constructivist approaches; (4) Results: The Kruskal-Wallis test showed significant differences in learning outcomes (p = 0.004), particularly between the multicultural and constructivist approaches (p = 0.009) and the humanistic and constructivist approaches (p = 0.005). Thematic analysis further revealed that the multicultural approach enhanced students’ understanding of tolerance and inclusivity, while the humanistic approach emphasized character-building and self-reflection in Islamic education; and (5) Conclusions: The humanistic and multicultural approaches were more effective in enhancing learning outcomes and pluralism understanding compared to the constructivist approach. The study’s findings highlight the need to strengthen instructional strategies that integrate humanistic and multicultural elements to improve the effectiveness of Islamic religious education in elementary schools.